Future governments - Stephens, Melodena; El-Sholkamy, Mona Mostafa; Moonesar, Immanuel Azaad; Awamleh, Raed (Emerald Publishing Limited, 2019)
Governments of today need to be future-oriented. The seismic disruptions in demographics, economic and political upheavals, increasing fragmentation between the haves and have-nots, leap-frog societal transformations, climate change, and technological innovations will be critical drivers impacting the context of how governments operate and function.Public sector organizations must be able to deliver services that are affordable, efficient and effective and can compete with the private sector. Governments must not only work towards safeguarding their people and resources, but take a more extensive look at the increasingly inter-connected world. They must work with the private sector and embrace the citizen who is demanding to be included in the decision-making process. This volume presents a series of case studies of countries, including the UAE, Germany, Estonia, Iceland, Finland, Chile and China, and their experiments with policy under five broad themes: government foresight, future orientation, regulatory reforms & strategy, the happiness agenda and the sharing economy. Each case, written by a leading expert in the field, presents the challenges and opportunities of the future and will provide key insights that will support policy makers, strategists and decision makers in mapping out their plans for tomorrow.- Resumé vydavatel
Includes index.
Keywords: politologie; strategický management; political science; strategic planning; elektronické knihy; případové studie; electronic books; case studies